Pengaruh Model Pembelajaran TGT Berbantuan Quizizz terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Al Wahida, Sabila Yusma; Sobiruddin, Dindin; Dimyati, Ahmad (Edumatica : Jurnal Pendidikan Matematika, 2024)
This research applies the Teams Games Tournament (TGT) learning model assisted by Quizizz, which can be a solution for teachers in optimizing students' mathematical problem-solving abilities. This research aims to determine the effect of applying the TGT model assisted by Quizizz on students' mathematical problem-solving abilities. This research is experimental research, with the research design used as a posttest-only control design. The population is all class VII students at MTs Negeri 2 Jakarta for the 2023/2024 academic year, consisting of seven classes. In this research, the sample used was 68 students who were divided into two classes (experimental class and control class). The instrument used in this research was a mathematical problem-solving ability test consisting of 7 descriptive questions. The results of the prerequisite tests for the analysis showed that the data in the experimental class was not normally distributed and had a homogeneous variance, so the data obtained in this study was analyzed using the Mann-Whitney non-parametric test. The results of this research show that students' mathematical problem-solving abilities that are applied using the TGT learning model assisted by Quizizz are higher than the mathematical problem-solving ability of students taught using conventional learning models, so there is an influence of the TGT learning model assisted by Quizizz on students' mathematical problem-solving ability.